2020
DOI: 10.1038/s41598-020-68693-w
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of indole production increases the activity of quinolone antibiotics against E. coli persisters

Abstract: Persisters are a sub-population of genetically sensitive bacteria that survive antibiotic treatment by entering a dormant state. The emergence of persisters from dormancy after antibiotic withdrawal leads to recurrent infection. Indole is an aromatic molecule with diverse signalling roles, including a role in persister formation. Here we demonstrate that indole stimulates the formation of Escherichia coli persisters against quinolone antibiotics which target the GyrA subunit of DNA gyrase. However, indole has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…However, in stationary phase, this phenomenon was reversed, with a higher proportion of persisters found in the Δ tnaA than in the parental strain, but mimics of persistent indole signaling restored the persister levels measured for the parental strain. Therefore, the Δ tnaA strain appears to be a high-persister-level mutant ( 21 ), exhibiting high persister levels in stationary but not in exponential phase, suggesting that persistent indole signaling increases the level of triggered persisters but not of spontaneous persisters ( 89 ). Surprisingly, we found that the abundance of VBNC cells within the E. coli population was not affected by the removal of either tryptophanase activity or indole signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, in stationary phase, this phenomenon was reversed, with a higher proportion of persisters found in the Δ tnaA than in the parental strain, but mimics of persistent indole signaling restored the persister levels measured for the parental strain. Therefore, the Δ tnaA strain appears to be a high-persister-level mutant ( 21 ), exhibiting high persister levels in stationary but not in exponential phase, suggesting that persistent indole signaling increases the level of triggered persisters but not of spontaneous persisters ( 89 ). Surprisingly, we found that the abundance of VBNC cells within the E. coli population was not affected by the removal of either tryptophanase activity or indole signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The reason behind this phenomenon may be that E. coli may utilize indole to compete against other microorganisms that could produce antibiotics ( Han et al, 2011 ). However, CIP is a member of synthetic quinolone antibiotics, and indole is reported to stimulate the formation of E. coli persisters against quinolone antibiotics ( Zarkan et al, 2020 ). We referred that CIP may in turn play a role through inhibiting indole production.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that although concentrations are below any toxic effect in humans, the presence of these agents has to be screened for safety issues [ 335 ]. Zarkan et al, found that inhibition of indole production increases the activity of quinolones against persisters of E. coli [ 336 ], probably by binding to the ATP binding site of GyrB subunit of DNA gyrase. The use of anti-virulence factors have been proposed as an antimicrobial therapy alternative to antibiotics [ 337 ].…”
Section: Recent Finding About Quinolonesmentioning
confidence: 99%